UJI EFEKTIVITAS ANTIHIPERGLIKEMIA KOMBINASI JUS MENTIMUN (Cucumis sativus Linn,) DAN JUS KACANG PANJANG (Vigna sinensis (L.) Savi Ex Has.) PADA TIKUS WISTAR JANTAN YANG DIINDUKSI SUKROSA - Pratama Lumban Tobing, Yoga; Robiyanto; Sari, Rafika (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2016)
Diabetes mellitus is metabolic disorder caused by high glucose level due to abnormalities in insulin secretions, work or both that can be caused by alpha-glucosidase and alpha-amylase in intestine. Cucumbers (Cucumis sativus) and cowpeas (Vigna sinensis) are reported as anti-diabetic. The objective of the present study was to determine the effectiveness of cucumber-cowpea juice combination with single juice and metformin on lowering blood glucose level. Rats were made hyperglycemic by induced sucrose 6,825 g/Kg BW orally. Sample was taken on the lateral vein rat tail. Blood glucose levels were observed before and after juice induction in 30, 60, 90, and 120 minutes by using glucometer. The results were analyzed by Mann-Whitney methods. Single cucumber juice 14,11 g/Kg BW and combination cowpea-cucumber juice 26,4 g/Kg BW – 42 g/Kg BW were given the optimum effect. Both the optimum dose have significant level with metformin as positive control (p>0,05). Results showed that the combination have significant level on lowering blood glucose level compared with metformin.